Beyond the discourse of denial: The reproduction of fossil fuel hegemony in Australia. (July 2021) - Wright, Christopher; Nyberg, Daniel; Bowden, Vanessa
Abstract: Despite growing public concern over the worsening climate crisis, tangible action to reduce carbon emissions and limit fossil fuel use remains limited. This is particularly apparent in carbon-rich nations which promote the extraction, export and use of coal, oil and gas as key drivers of economic activity. We examine this contradiction between growing public demands for climate action and the continued dominance of fossil energy in Australia, now the world's largest exporter of coal and gas. Through a qualitative analysis of media coverage and industry public relations during the period 2008–2019, we show how the fossil fuel hegemony has been maintained and extended in the face of growing social and political critique. We identify the key discourses that the Australian fossil fuel sector has employed in reproducing hegemony and delaying action on climate change. This extends previous theorisations of moral and intellectual leadership by detailing how the fossil fuel sector embeds particular technical claims into the climate change debate. Second, we expand knowledge of political strategy to show how corporate discourses aimed at maintaining hegemony are extended through the state as an ideological promoter.